Facial mimicry and the mirror neuron system: simultaneous acquisition of facial electromyography and functional magnetic resonance imaging - Likowski, Katja U.; Muehlberger, Andreas; Gerdes, Antje B.; Wieser, Matthias J.; Pauli, Paul; Weyers, Peter (Frontiers in Human Neuroscience, 2012)
Numerous studies have shown that humans automatically react with congruent facial reactions, i.e. facial mimicry, when seeing a vis-á-vis’ facial expressions. The current experiment is the first investigating the neuronal structures responsible for differences in the occurrence of such facial mimicry reactions by simultaneously measuring BOLD and facial EMG in an MRI scanner. Therefore, 20 female students viewed emotional facial expressions (happy, sad, and angry) of male and female avatar characters. During Differentiation presentation, the BOLD signal as well as M. zygomaticus major and M. corrugator supercilii activity were recorded simultaneously. Results show prototypical patterns of facial mimicry after correction for MR-related artifacts: enhanced M. zygomaticus major activity in response to happy and enhanced M. corrugator supercilii activity in response to sad and angry expressions. Regression analyses show that these congruent facial reactions correlate significantly with activations in the IFG, SMA and cerebellum. Stronger zygomaticus reactions to happy faces were further associated to increased activities in the caudate, MTG and PCC. Corrugator reactions to angry expressions were further correlated with the hippocampus, insula and STS. Results are discussed in relation to core and extended models of the mirror neuron system.